Annual Report on Exchange Arrangements and Exchange Restrictions 1965. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1965)
This paper outlines the changes that took place in restrictive systems were largely a reflection of shifts in the balance of payments positions and outlook of member countries. The country surveys show that these changes were numerous. Several countries, including the United Kingdom and the United States, took steps to moderate capital outflows. The range of restrictive devices applied by some countries appears to have widened in recent years. The use of advance import deposit requirements has spread, and more countries are applying surcharges to imports when in balance of payments difficulties. In contrast, a number of member countries whose restrictive systems have been progressively liberalized in recent years have relied on internal measures to meet temporary balance of payments difficulties rather than resort to restrictions. By making use of the IMF's resources several member countries have been able to maintain or extend their liberalization policies.